Evaluasi Akurasi Sales Forecasting dan Realisasi Penjualan Batako pada UD Budi Ayu Banjarmasin - Noor Mutia; Noor Safrina; Rizky Amelia (Indonesian Journal of Applied Accounting and Finance, 2025)
This study aims to evaluate the effectiveness of sales forecasting methods in predicting the sales of concrete bricks at UD Budi Ayu Banjarmasin, as well as to identify the issues faced by the company in sales planning. The research problem addressed is the inaccuracy in sales projections that can affect the company's strategic decisions. The research method employed is a quantitative descriptive approach, analyzing historical sales data from 2020 to 2024, and applying three forecasting methods: least squares, moment, and quadratic. Findings indicate that the least squares and moment methods yield higher accuracy in predicting sales of floor concrete bricks, while the quadratic method is more effective for wall concrete brick sales. The implications of this research highlight the importance of selecting the appropriate forecasting method to enhance sales prediction accuracy, which in turn can assist the company in budget planning and making better strategic decisions. This study is expected to provide practical contributions for manufacturing companies in optimizing sales strategies and improving overall business performance.